Research Progress and Engineering Applications of Stainless Steel-Reinforced Concrete Structures - Jian Yuan; Zhinan Ou (Advances in Civil Engineering)
The durability of concrete structures can effectively be enhanced by using stainless steel rather than ordinary steel reinforcements under harsh service conditions. Because the basic mechanical properties and stress-strain relationship of stainless steel reinforcements obviously differ from those of ordinary steel reinforcements, the current design codes for reinforced concrete structures are not appropriate for stainless steel-reinforced concrete. On the basis of the research works reported in the past decades, this paper systematically summarizes and analyzes the mechanical properties and corrosion resistance of stainless steel reinforcements, the properties of the bond between stainless steel reinforcements and concrete, the mechanical properties of stainless steel-reinforced concrete members, and the application of stainless steel reinforcements in practical engineering and proposes relevant problems which should be examined further. It is suggested that the design theory of stainless steel-reinforced concrete structures should be further improved to take full advantage of these structures.